DESIGN FEATURES OF THE EXPERIMENTAL UNIT AND NUMERICAL STUDIES OF BIOMASS THER-MOCHEMICAL PROCESSING. PART 3 THE INFLUENCE OF HEAT CAPACITY AND THERMAL DECAY EFFECT ON THE HEATING RATE OF WOOD BIRCH PARTICLE BED - Rokhman , B. B.; Kobzar , S. G. (Institute of Renewable Energy National Academy of Sciences of Ukraine, 2024)
The third part of this work is devoted to the theoretical study of the influence of biomass heat capacity, boundary conditions, recirculation of pyrolysis gases, external and internal heat flows on the heating time of a fixed pyrolysis bed consisting of Wood Birch particles of 10 mm equivalent diameter. Three options for heating the bed were considered: a) electric heating of the outer and inner surfaces of the pyrolyzer; b) electric heating of the outer surface and heating the inner surface of the pyrolyzer by combustion products; c) two electric heaters and recirculating pyrolysis gas with a temperature of 800 °С. It is shown that: 1) taking into account the thermal decomposition thermal effect in the equation of thermal energy of particles leads to a decrease in the biomass bed heating time by 1.33 times and an increase in the bed heating rate to 987 °С/min; 2) recirculation of high-temperature pyrolysis gases entering the pyrolyzer limited by the outer D = 220 mm and inner d = 150 mm diameters, reduces the bed heating time by 1.39 times, resulting in increasing the particle heating rate from 987 to 1373 °С/min; 3) pyrolysis gases recirculation contributes to the rapid pyrolysis organization when the pyrolyzer outer diameter increases from 220 to 240 mm and from 220 to 300 mm, resulting in a decrease in the bed heating rate from 1373 to 1295.3 °С/min and from 1373 to 1223 °С/min, respectively; 4) the calculated composition of the mixed pyrolysis gas at tg = 800 °С: CO2 = 7.14 %, CO = 51.4 %, H2 = 15.56 %, C1.16H4 = 23.72 % (CH4 = 16.6 % and C2H4 = 7.116 %), N2 = 0.296 %), is in good agreement with the results of the Wood Birch pyrolysis experiment at tg = 800 °С: CO2 = 8.3 %, CO = 50.70 %, H2 = 16.8 %, CH4 = 16.2 % and C2H4 = 7.9 %.